Aligning the quantum perspective of learning to instructional design: Exploring the seven definitive questions - Katherine Joyce Janzen (Athabasca University Press, 2011)
TThis paper builds upon a foundational paper (under review) which explores the rudiments of the quantum perspective of learning. The quantum perspective of learning uses the principles of exchange theory or borrowed theory from the field of quantum holism pioneered by quantum physicist David Bohm (1971, 1973) to understand learning in a new way. Bohm proposes that everything exists as wholes, rather than as parts, and that everything is connected. Similarly, the quantum perspective of learning proposes that individuals learn in holistic ways as they interact with temporal and in infinitely extending virtual worlds. Further, according to the quantum perspective of learning, learners have infinite potential. In this paper, the quantum perspective of learning is examined utilizing a combination of Schunk’s (1991) and Ertmer and Newby’s (1993) definitive questions for aligning learning theory with instructional design. These seven definitive questions focus on how learning happens, influential factors in learning, the role of memory, transfer of knowledge, modalities of learning that can best explain the quantum  perspective of learning, applicable assumptions, and a discussion of how instruction can be organized to optimize learning. Examples of strategies that facilitate the quantum perspective of learning are provided.